2003
DOI: 10.1271/bbb.67.758
|View full text |Cite
|
Sign up to set email alerts
|

Dietary Fructooligosaccharides Induce Immunoregulation of Intestinal IgA Secretion by Murine Peyer's Patch Cells

Abstract: Probiotic supplements induce immunological responses in the host, and dietary fructooligosaccharides (FOS) stimulate the growth of selected intestinal microflora. In this study we investigated the immunological influences of orally administrated FOS. BALB/c mice were orally administered 0-7.5% FOS for 6 weeks, and the intestinal mucosal immune responses were measured. In the 2.5%-FOS group, fecal IgA was significantly increased. IgA secretion by Peyer's patch (PP) cells was upregulated in a dose-dependent way … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

21
150
4
5

Year Published

2004
2004
2014
2014

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 197 publications
(180 citation statements)
references
References 36 publications
21
150
4
5
Order By: Relevance
“…The present study showed that maternal supplementation with 1-kestose significantly increased the amount of total IgA in the intestinal tracts of lactating mice (Table 3), supporting previous reports [12][13][14] that dietary FOS or 1-kestose intensifies IgA production in the digestive tract. The authors had also previously confirmed that dietary FOS promotes IgA + B cell class switching in the Peyer's patches of the small intestine, 13) 16) Considering that the fecal Bacteroides count was higher in the 1-kestose-supplemented group than the control group, in the present study (Table 2), the increase in IgA levels in the intestinal mucosa might be caused by an increased number of IgA-producing plasma cells in the digestive tract.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…The present study showed that maternal supplementation with 1-kestose significantly increased the amount of total IgA in the intestinal tracts of lactating mice (Table 3), supporting previous reports [12][13][14] that dietary FOS or 1-kestose intensifies IgA production in the digestive tract. The authors had also previously confirmed that dietary FOS promotes IgA + B cell class switching in the Peyer's patches of the small intestine, 13) 16) Considering that the fecal Bacteroides count was higher in the 1-kestose-supplemented group than the control group, in the present study (Table 2), the increase in IgA levels in the intestinal mucosa might be caused by an increased number of IgA-producing plasma cells in the digestive tract.…”
Section: Discussionsupporting
confidence: 92%
“…11) Several studies have shown that supplementation with 1-kestose or FOS leads to increased production of IgA in the digestive tract of rodents. [12][13][14][15] In animals, intestinal microbiota can affect intestinal IgA levels. Previous reports have shown the existence of a relationship between the cecal lactobacilli count and intestinal IgA levels in rats.…”
mentioning
confidence: 99%
“…Field et al, 1999;Schley and Field, 2002;Hosono et al, 2003). In this study, leukocyte counts in peripheral blood were decreased in lactulosetreated calves and monocyte numbers were decreased in both treatment groups.…”
Section: Discussionsupporting
confidence: 47%
“…The ileum wall is interstratified with Peyer's patches, parts of the gut-associated lymphoid tissue. Cells from these patches have been shown to release anti-inflammatory cytokines such as IL10 after stimulation with probiotics, prebiotics or fermentation products thereof (Sä emann et al, 2000;Hosono et al, 2003;Roller et al, 2004). Therefore, it seems probable that fermentation products deriving from inulin degradation or secretory molecules from bacteria stimulated by inulin feeding are causative agents in this increase of IL10 expression.…”
Section: Discussionmentioning
confidence: 99%
“…Neither was lymphocyte proliferation altered in the spleen of rats supplemented with OF-enriched IN (49) nor splenocyte proliferation in mice vaccinated against Salmonella typhimurium and supplemented with OF in combination with IN with shorter-chain FOS removed (47) . Thus, lymphocyte proliferation in the spleen appears not to be susceptible to modification by b2-1 fructans.As in the GALT, T cell cytokine production may be altered with b2-1 fructan supplementation: IFN-g production from spleen CD4 þ T cells was increased in mice supplemented with FOS, although IL-5 and IL-6 production were decreased (51) , and IL-12 and IFN-g production from splenocytes was increased upon supplementation with a combination of OF and IN with shorter-chain FOS removed in mice, although TNF-a production was not altered (47) . There was no effect of OFenriched IN supplementation in rats upon IL-10 production by splenocytes (57) , or upon cytokine production in the spleen (49) .…”
mentioning
confidence: 99%